Muhammadiyah and Nahdlatul Ulama Education: Two Main Pillars of National Education in Indonesia - Tasman Hamami (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
Muhammadiyah and NU are the mainstream Islamic social organizations established before the Indonesian independence. These organizations drive the renewal of Islamic thought, da'wah, social, health, and education. They have thousands of educational institutions spread throughout Indonesia and play an important role in the development of Islamic education, so they are the main pillars of National Education. This study aimed to discuss the role and contribution of Muhammadiyah and NU as pillars of national and Islamic education. A historical approach through source search (heuristics), assessment (criticism), and construction was used. Through an integrative and modern Islamic education system, the results showed that Muhammadiyah had opened the minds of Muslims and the Indonesian people about the importance of religion and science to realize a progressive Islamic society. Furthermore, NU prioritizes the education system of traditional pesantren and madrasas and has instilled basic Islamic teachings in shaping the morals of Muslims and the Indonesian nation. Therefore, Muhammadiyah and NU education contribute to religious moderation (Islam wasathiyah) and pillars of national education. The results of this study have implications for the development of any National Education policy that cannot deny the roles of Muhammadiyah and NU.